Dampak Sistem Zonasi pada Penerimaan Siswa Baru Sekolah Menengah Pertama terhadap Minat Belajar Siswa Kelas 6 - Risca Candra Vinalistyosari; Anang Santoso; Radeni Sukma Indra Dewi (Journal on Education, 2023)
The Impact of Zoning System on the Admission of New Junior High School Students on the Learning Interest of Grade 6 Students. Amidst the dynamics of education in Indonesia, the zoning system has become a prominent topic of conversation policy innovations, especially in the context of new student admissions at Junior High Schools (SMP). This policy aims to promote educational equity and reduce social disparities. The zoning system prioritizes students who live near the schools, with the goal of creating a fairer distribution of education and reducing transportation costs for students. In the context of the zoning system for new student admissions to SMP, there are significant impacts that can be felt by 6th-grade elementary school students (SD). The first impact is the change in aspirations for the school of choice. Before the implementation of the zoning system, many 6th-grade students had dream schools they had long aspired to attend. However, with the zoning system in place, those school choices may no longer be accessible due to the geographical location factor of their residence.